Current Archaeological Research in Israel: Ancient Agricultural Settlement and Religion in the Uvda Valley in Southern Israel - Avner, Uzi (1990)
In spite of extremely arid conditions, the Uvda Valley in the southern Negev has been the site of a flourishing agricultural society dating back four to six thousand years. Four years of survey and excavation in the region have also revealed evidence of many cult sites. How could agriculture thrive in such a severe climate, and what can these cult sites tell us about the religious life of the ancient desert inhabitants?